Dedifferentiation, Proliferation, and Redifferentiation of Adult Mammalian Cardiomyocytes After Ischemic Injury. Issue 9 (29th August 2017) - Wang, Wei Eric; Li, Liangpeng; Xia, Xuewei; Fu, Wenbin; Liao, Qiao; Lan, Cong; Yang, Dezhong; Chen, Hongmei; Yue, Rongchuan; Zeng, Cindy; Zhou, Lin; Zhou, Bin; et al.
Abstract : Background: Adult mammalian hearts have a limited ability to generate new cardiomyocytes. Proliferation of existing adult cardiomyocytes (ACMs) is a potential source of new cardiomyocytes. Understanding the fundamental biology of ACM proliferation could be of great clinical significance for treating myocardial infarction (MI). We aim to understand the process and regulation of ACM proliferation and its role in new cardiomyocyte formation of post-MI mouse hearts. Methods: β-Actin-green fluorescent protein transgenic mice and fate-mapping Myh6-MerCreMer-tdTomato/lacZ mice were used to trace the fate of ACMs. In a coculture system with neonatal rat ventricular myocytes, ACM proliferation was documented with clear evidence of cytokinesis observed with time-lapse imaging. Cardiomyocyte proliferation in the adult mouse post-MI heart was detected by cell cycle markers and 5-ethynyl-2-deoxyuridine incorporation analysis. Echocardiography was used to measure cardiac function, and histology was performed to determine infarction size. Results: In vitro, mononucleated and bi/multinucleated ACMs were able to proliferate at a similar rate (7.0%) in the coculture. Dedifferentiation proceeded ACM proliferation, which was followed by redifferentiation. Redifferentiation was essential to endow the daughter cells with cardiomyocyte contractile function. Intercellular propagation of Ca 2+ from contracting neonatal rat ventricular myocytes into ACM daughter cells was required to activate the Ca 2+ -dependent calcineurin-nuclear factor of activated T-cell signaling pathway to induce ACM redifferentiation. The properties of neonatal rat ventricular myocyte Ca 2+ transients influenced the rate of ACM redifferentiation. Hypoxia impaired the function of gap junctions by dephosphorylating its component protein connexin 43, the major mediator of intercellular Ca 2+ propagation between cardiomyocytes, thereby impairing ACM redifferentiation. In vivo, ACM proliferation was found primarily in the MI border zone. An ischemia-resistant connexin 43 mutant enhanced the redifferentiation of ACM-derived new cardiomyocytes after MI and improved cardiac function. Conclusions: Mature ACMs can reenter the cell cycle and form new cardiomyocytes through a 3-step process: dedifferentiation, proliferation, and redifferentiation. Intercellular Ca 2+ signal from neighboring functioning cardiomyocytes through gap junctions induces the redifferentiation process. This novel mechanism contributes to new cardiomyocyte formation in post-MI hearts in mammals. Abstract : Supplemental Digital Content is available in the text.